Use of contraception during first sexual intercourse among Norwegian adolescents: a national cross-sectional study - Live Solveig Nordhagen; Hilde Egge; Marja Leonhardt (BMC, 2024)
Abstract Background Most Norwegian adolescents experience their first sexual intercourse during late adolescence. Use of contraception is important to avoid unwanted pregnancy, while condoms can also protect against sexually transmitted diseases. There are few studies on the use of contraception at first sexual intercourse, most with varying results, and some studies have only examined the use of contraception among girls. In our study, we aimed to determine the use of contraception at first sexual intercourse, and to investigate associations between use of contraceptives at first sexual intercourse, sociodemographic factors, and alcohol and other substance use. Methods The study was based on data from the national electronic youth survey Ungdata, conducted in 2020-2022 among 113 049 upper secondary pupils (15-19 years) in Norway, which was around 65% of pupils attending upper secondary school during the study period. Descriptive analysis was used to estimate the prevalence of contraceptive use at first sexual intercourse, and multivariate logistic regression analyses to investigate the association between contraceptive use, sociodemographic factors, and alcohol intoxication and substance use. Result 32% of Norwegian adolescents did not use contraception at first sexual intercourse. More girls (57.4%) than boys (42.6%) reported use of contraception. Factors associated with non-use of contraception during first sexual intercourse among boys were having parents with no college /university education (OR = 1.22: CI 1.13-1.32), perceived poor family finances (OR = 1.22: CI 1.06-1.40), alcohol intoxication, and use of cannabis or other narcotic substances during the past 12 months. The same factors were associated with non-use of contraception among girls. Additionally, being older than 16 years (OR = 1.13: CI 1.06-1.19) was also associated with non-use of contraception at first sexual intercourse. Conclusion Many adolescents did not use contraception at first sexual intercourse. Alcohol intoxication and use of cannabis or other narcotic substances were associated with a lower likelihood of using contraceptives. This highlights the importance of preventive efforts including earlier prevention education that focuses more on the consequences of not using contraception in order to prevent unwanted pregnancies and sexually transmitted infections.